2015
DOI: 10.1007/s10143-015-0643-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a method to determine deep brain stimulation targets using deterministic tractography in a navigation system

Abstract: Recent advances in imaging permit radiologic identification of target structures for deep brain stimulation (DBS) for movement disorders. However, these methods cannot detect the internal subdivision and thus cannot determine the appropriate DBS target located within those subdivisions. The aim of this study is to provide a straightforward method to obtain an optimized target (OT) within DBS target nuclei using a widely available navigation system. We used T1- and T2-weighted images, fluid-attenuated inversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…This arrangement was also observed in another 3 T functional and structural connectivity study based on averaged data of healthy subjects, but could not be demonstrated consistently in all individual subjects (Brunenberg et al, 2012). Finally the STN’s connectivity was previously investigated in PD patients as well, although this only concerned its motor area and analyses were only performed in a qualitative manner (Avecillas-Chasin et al, 2015). Here, we show that the three zones can also be objectively and quantitatively identified in patients with PD and, importantly, on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement was also observed in another 3 T functional and structural connectivity study based on averaged data of healthy subjects, but could not be demonstrated consistently in all individual subjects (Brunenberg et al, 2012). Finally the STN’s connectivity was previously investigated in PD patients as well, although this only concerned its motor area and analyses were only performed in a qualitative manner (Avecillas-Chasin et al, 2015). Here, we show that the three zones can also be objectively and quantitatively identified in patients with PD and, importantly, on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…Such diffusion-based tractography has already been used to examine the tissue and pathways targeted in DBS treatment [6], [49]. These advanced techniques allow for detailed delineation of the connections between the STN (and GPi), cortex and other basal ganglia structures at the individual patient level.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Regarding the tractography methods, previous methods are based on iterative deterministic assessments, which is prone to sampling limitations (Avecillas-Chasin et al, 2015; Choi et al, 2015). While the probabilistic approach is time intensive, the data-driven nature may be more practical and provide advantages over a manual iterative approach.…”
Section: Discussionmentioning
confidence: 99%